2019
DOI: 10.3390/jcm8030388
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Colorectal Cancer Cell Lines to Enterococcus faecalis’ Strains Isolated from Healthy Donors and Colorectal Cancer Patients

Abstract: The metabolites produced by the host’s gut microbiota have an important role in the maintenance of intestinal homeostasis, but can also act as toxins and induce DNA damage in colorectal epithelial cells increasing the colorectal cancer (CRC) chance. In this scenario, the impact of some of the components of the natural human gastrointestinal microbiota, such as Enterococcus faecalis (E. faecalis), at the onset of CRC progression remains controversial. Since under dysbiotic conditions it could turn into a pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…It has been shown that MED13 could directly link a cyclin-dependent kinase 8 (CDK8) module to Mediator 81,82 , which is a colorectal cancer oncogene, amplified in colorectal tumours and activating transcription driving colon tumorigenesis leading to CRC 58 . This could explain a long suspected link between Enterococcus faecalis and development of CRC after having been found in higher concentrations in CRC patients than healthy individuals 51-55 . The suspected mode of action of E. faecalis on CRC development is currently unclear, but could be linked to extracellular free radical production directly leading to DNA break, point mutation and chromosomal instability in colorectal cells 56 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MED13 could directly link a cyclin-dependent kinase 8 (CDK8) module to Mediator 81,82 , which is a colorectal cancer oncogene, amplified in colorectal tumours and activating transcription driving colon tumorigenesis leading to CRC 58 . This could explain a long suspected link between Enterococcus faecalis and development of CRC after having been found in higher concentrations in CRC patients than healthy individuals 51-55 . The suspected mode of action of E. faecalis on CRC development is currently unclear, but could be linked to extracellular free radical production directly leading to DNA break, point mutation and chromosomal instability in colorectal cells 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The SCFAs in the samples were analyzed as free acid form using a Supelco Nukol column 30 m length, 0.25 mm internal diameter and 0.25 µm of film thickness with the temperatures program as follows: Initial temperature of 40 °C was held for 1 min, then it was increased to 150 °C at 30 °C/min, finally grow up to 220 °C at 20 °C/min[26]. A 1 µL aliquot of extracted sample was injected in splitless mode (splitless time 1 min) at 250 °C, while the transfer line temperature was 280 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the heat‐killed E. faecalis strain KH2 may attenuate NLRP3 inflammasome activation in macrophages and ameliorate the severity of dextran sulfate sodium‐induced colitis and the development of colitis‐associated CRC in mice 47 . These conflicting roles of E. faecalis in CRC development may be attributed to the different isolated and investigated strains 48,49 . Given that obesity leads to increased risk for CRC, the authors of the present study speculated that reduced E. faecalis in obese patients with CRC could be a promoting factor for the development of obesity‐related CRC.…”
Section: Discussionmentioning
confidence: 78%
“…47 These conflicting roles of E. faecalis in CRC development may be attributed to the different isolated and investigated strains. 48,49 Given that obesity leads to increased risk for CRC, the authors of the present study speculated that reduced E. faecalis in obese patients with CRC could be a promoting factor for the development of obesity-related CRC.…”
Section: Discussionmentioning
confidence: 80%